Contemporary lymphatic interventions for post-operative lymphatic leaks - Majdalany, Bill S.; El-Haddad, Ghassan (Translational andrology and urology, 2020)
Post-operative lymphatic injuries are uncommon but increase morbidity and mortality in vulnerable patient populations. Post-surgical lymphatic leaks are most commonly a consequence of radical neck dissection, esophagectomy, and lung cancer resections or retroperitoneal surgeries such as radical nephrectomy and lymphadenectomy. Injury may occur anywhere along the lymphatic chains with most serious leaks occurring along the axial skeleton between the inguinal region and the left venous angle. The resultant clinical manifestations of a lymphatic leak are dependent on the location and severity of the lymphatic injury as well as patient factors. Treatment strategies are tailored toward the causative etiology, symptom severity, and daily leak volume with higher volume leaks warranting a more aggressive approach. Lymphangiography and lymphatic interventions, such as embolization, are increasingly applied for both the diagnosis and as a minimally invasive therapy for lymphatic injuries. Herein, a review of lymphatic anatomy, lymphangiography, and lymphatic interventions for the treatment of post-operative chylothorax, chylous ascites, and lymphocele is presented.